PHF6 Mutations in Hematologic Malignancies - Kurzer, Jason H.; Weinberg, Olga K. (Frontiers in Oncology, 2021)
Next generation sequencing has uncovered several genes with associated mutations in hematologic malignancies that can serve as potential biomarkers of disease. Keeping abreast of these genes is therefore of paramount importance in the field of hematology. This review focuses on PHF6, a highly conserved epigenetic transcriptional regulator that is important for neurodevelopment and hematopoiesis. PHF6 serves as tumor suppressor protein, with PHF6 mutations and deletions often implicated in the development of T-lymphoblastic leukemia and less frequently in acute myeloid leukemia and other myeloid neoplasms. PHF6 inactivation appears to be an early event in T-lymphoblastic leukemogenesis, requiring cooperating events, including NOTCH1 mutations or overexpression of TLX1 and TLX3 for full disease development. In contrast, PHF6 mutations tend to occur later in myeloid malignancies, are frequently accompanied by RUNX1 mutations, and are often associated with disease progression. Moreover, PHF6 appears to play a role in lineage plasticity within hematopoietic malignancies, with PHF6 mutations commonly present in mixed phenotype acute leukemias with a predilection for T-lineage marker expression. Due to conflicting data, the prognostic significance of PHF6 mutations remains unclear, with a subset of studies showing no significant difference in outcomes compared to malignancies with wild-type PHF6, and other studies showing inferior outcomes in certain patients with mutated PHF6. Future studies are necessary to elucidate the role PHF6 plays in development of T-lymphoblastic leukemia, progression of myeloid malignancies, and its overall prognostic significance in hematopoietic neoplasms.